Practical vignetting correction method for digital camera with measurement of surface luminance distribution. Issue 8 (November 2016) - Kordecki, Andrzej; Palus, Henryk; Bal, Artur
Abstract Vignetting refers to the fall-off pixel intensity from the centre towards the edges of the image. This effect is undesirable in image processing and analysis. In the literature, the most commonly used methods of vignetting correction assume radial characteristic of vignetting. In the case of camera lens systems with non-radial vignetting, such approach leads to insufficient correction. Additionally, the majority of vignetting correction methods need a reference image acquired from a uniformly illuminated scene, what can be difficult to achieve. In this paper, we propose a new method of vignetting correction based on the local parabolic model of non-radial vignetting and compensation of non-uniformity of scene luminance. The new method was tested on camera lens system with non-radial vignetting and non-uniformly illuminated scene. In these conditions, the proposed method gave the best correction results among the tested methods.